Perbedaan Hasil Pemeriksaan Glukosa Darah dan Urine pada Pasien Diabetes Melitus Type 2 di Laboratorium Rumah Sakit Santa Elisabeth Medan. - Asti Handayani Br Tarigan; Anak agung Ayu Eka Cahyani; Putu Ayu Parwati (PT. GIAT KONSELING NUSANTARA, 2025)
Diabetes mellitus (DM) is a chronic disease characterized by higher than normal blood glucose levels caused by the pancreas not producing enough insulin or the body's inability to use the insulin that has been produced. This study aims to determine the differences in blood and urine glucose test results in type 2 diabetes mellitus patients at the Santa Elisabeth Hospital Laboratory in Medan. The type of research used is quantitative research with an experimental approach. The number of samples was 40 inpatients at Santa Elisabeth Hospital in Medan. The results of this study showed a dominant female gender of 25 people (62.5%) and a dominant age of 54-56 years as many as 12 people (30.0%). Statistical analysis of the Mann Whitnety test obtained a p-value of 0.001 so it can beconcluded that there are differences in blood glucose and urine glucose tests in Type 2 Diabetes Mellitus patients. Although urine glucose tests can provide additional information about glucose control, blood glucose tests remain a more effective way to monitor patient conditions. Therefore, the management of Diabetes Mellitus must be carried out comprehensively by considering regular blood glucose checks and paying attention to the patient's kidney condition.